(untitled) (Asian Journal of Social Science Studies, 2022)
With the rapid development of the Internet in China in recent years, the public tends to get information about news events from the Internet and publish their opinions on online social platforms. Guiding people’s public opinion in the online world has become an essential social proposition. We choose the "Bao Yuming’s alleged sexual assault case," which caused an intense social discussion on the Chinese Internet in 2020, as a case study for analysis and analysis of the various public opinion phenomena that emerged in society at that time discuss their causes and background. Finally, we propose ways to guide the case from three aspects.